Spin-3/2 Ising model on a two-layer Bethe lattice with FM/AFM interactions - Albayrak, E.; Yigit, A. (Condensed Matter Physics, 2009)
Two-layer Bethe lattice whose lattice sites are occupied with spin-3/2 atoms is solved exactly by using the
recursion relations in a pairwise approach for given coordination numbers q = 3, 4 and 6 with equal external
magnetic fields acting on the layers. The ferromagnetic (FM) and antiferromagnetic (AFM) interactions for the
spins of the upper and lower layers, respectively, and either FM or AFM type interactions between the adjacent
spins of the layers are assumed. The phase diagrams of the model are studied on different planes for given
system parameters by obtaining the ground state (GS) phase diagrams and the thermal variations of the order
parameters and the response functions, i. e. the susceptibility and the specific heat, in detail. It was found that
the model presents both second- and first-order phase transitions. The reentrant behavior is seen when the
model presents two N´eel temperatures for higher q values. The existence of the tricritical point and critical end
points is also confirmed. Двошарова гратка Бете з вузлами, зайнятими атомами зi спiном 3/2, є точно розв’язаною, використовуючи рекурентнi спiввiдношення у парному пiдходi з однаковими магнiтними полями, що дiють на шари. Припускається, що спiни верхнього i нижнього шарiв мають вiдповiдно, феромагнiтнi (ФМ) та антиферомагнiтнi (АФМ) взаємодiї, а взаємодiя мiж сусiднiми спiнами шарiв є ФМ або АФМ типу. Вивчаються фазовi дiаграми моделi на рiзних площинах для даного набору системних параметрiв шляхом отримання основного стану фазової дiаграми i температурних змiн параметрiв порядку та функцiй вiдгуку, зокрема, сприйнятливостi i питомої теплоємностi. Показано, що модель демонструє фазовi переходи як другого, так першого роду. Видно реверсивну поведiнку, коли модель демонструє двi температури Нееля для вищих значень q. Також отримано трикритичну точку i критичну кiнцеву точку.